Physical treatment in ankle injures - review of the literature - Magdalena Weber-Rajek; Katarzyna Ciechanowska; Irena Bułatowicz; Agnieszka Radzimińska; Katarzyna Strojek; Walery Zukow (Journal of Education, Health and Sport, 2023)
Physical treatment in ankle injures - review of the literature